PARÂMETROS OPERACIONAIS PARA IMPLANTAÇÃO DE UMA RECICLADORA DE PNEUS INSERVÍVEIS EM SANTA MARIA – RS - Libera, Fabiano Viero Della; Zanini, Marco Antônio; Rossato, Marivane Vestena; Guse, Jaqueline Carla; Dörr, Andréa Cristina (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2012)
http://dx.doi.org/10.5902/223611704972 The inadequate discarding of inservíveis tires has brought curses it human being. In thiscontext, the necessity appears to know alternatives as the implantation of recicladora ofinservíveis tires, the city proposal is Saint Maria, RS. The present work looked for to evidence thenecessary operational parameters through the exploratório study, using the techniques ofdocumentary analysis and content. One presents, the costs for acquisition of machines,installations and hand of monthly workmanship. The production is divided in rubber and steel,being that the steel has certain purchaser. The recicladora is presented as viable alternative forpresenting profit and bringing ambient benefits.